Cycle performance of air conditioning system based on finned tube heat exchangers with different helix angles. (5th March 2015) - Wang, Shuangfeng; Ke, Hongfeng; Li, Xuanyou; Cheng, Song
Abstract: The cycle performance of the novel 5 mm outer diameter (OD) finned tube heat exchangers (FTHX) with different helix angles (1°, 6°) were investigated as indoor unit in split air conditioning systems to be compared with those of the conventional indoor ones (5 mm and 7 mm FTHX with helix angle of 18°). Conventional T-splitter of the outdoor heat exchanger (HX) was afterward replaced by a Y-splitter and numbers of U-tubes in the two bypasses were adjusted to balance the heat exchange amount of two different bypasses. At first, experimental results showed that the 5 mm system with helix angle of 6° was superior to those 5 mm systems with helix angles of 1° and 18° but still inferior to the conventional 7 mm system, in aspects of capacity and coefficient of performance (COP) both in cooling and heating mode. But after the adjustments, performance of the 5 mm system with helix angle of 6° experienced a 1.5% and 0.7% higher capacity both in cooling and heating mode, respectively, and a 1.7% higher heating COP in spite of a 0.7% lower cooling COP. The system adopting the 5 mm tubes with the helix angle of 6° after adjustments is demonstrated that it can commendably ease material pressure and meanwhile promote the cycle performance. Highlights: Two kinds of 5 mm finned tubes with different helix angles are proposed. Comparisons are made between systems based on the proposed and conventional tubes. The cycle of the outdoor heat exchanger is adjusted. Material cost of the adjusted air conditioner system is proved less.